2022
DOI: 10.3390/plants12010005
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Zerumbone: From Natural Sources to Strategies to Improve Its Bioavailability and Oral Administration

Abstract: Zerumbone is a multifunctional compound with antimicrobial, antitumor, hyperalgesic, antioxidant and anti-inflammatory applications, and constitutes a point molecule for the future synthesis of derivatives with improved efficiency. This monocyclic sesquiterpenoid is found in high content in wild ginger (Zingiber zerumbet Smith), a perennial herb with economic importance as an ornamental as well as a medicinal plant. The presence of zerumbone is a distinctive feature that allows identification and differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 141 publications
0
4
0
Order By: Relevance
“…Zerumbone strongly inhibited the oxidative burst of zymosan and phorbol myristate 13-acetate (PMA)-stimulated neutrophils. It significantly decreased extracellular ROS generation in PMNs, with an IC 50 value of 17.36 M, comparable to aspirin ( Akhtar et al, 2019 ; Ibanez et al, 2023 ). Zerumbone was also effective against fluconazole-resistant and fluconazole-susceptible Candida albicans biofilms and disrupted the extracellular matrix ( Abreu-Pereira et al, 2023 ).…”
Section: Immunomodulating Effects and Mechanisms Of Bioactive Metabol...mentioning
confidence: 81%
“…Zerumbone strongly inhibited the oxidative burst of zymosan and phorbol myristate 13-acetate (PMA)-stimulated neutrophils. It significantly decreased extracellular ROS generation in PMNs, with an IC 50 value of 17.36 M, comparable to aspirin ( Akhtar et al, 2019 ; Ibanez et al, 2023 ). Zerumbone was also effective against fluconazole-resistant and fluconazole-susceptible Candida albicans biofilms and disrupted the extracellular matrix ( Abreu-Pereira et al, 2023 ).…”
Section: Immunomodulating Effects and Mechanisms Of Bioactive Metabol...mentioning
confidence: 81%
“…ZER is a naturally occurring sesquiterpene present abundantly in the rhizome of Zingiber Zerumbet (L.) Smith. Since its first isolation in 1960, numerous studies have been conducted to elucidate the medicinal values of ZER, such as immunomodulatory, anti-inflammatory, antioxidant, antimicrobial, antiproliferative, and anticancer activities [22]. The anticancer potential of ZER has been demonstrated against several types of cancers, including breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…ZER induces cell cycle arrest and apoptosis in breast cancer cells by activating the pro-apoptotic proteins, Bax and Bak [23]. However, the therapeutic application of ZER is greatly limited by its poor water solubility [22]. To overcome this limitation, Rahman and co-workers devised a strategy to encapsulate ZER in a biocompatible and biodegradable NLC [24].…”
Section: Introductionmentioning
confidence: 99%
“…According to Koga et al (2016), terpenes and polyphenols are the primary chemical components found to dominate in lempuyang, with the main bioactive compound being zerumbone. Zerumbone is a valuable compound with various biological functions, including anti-bacterial capabilities (Veena et al, 2020;Ibáñez et al, 2023). Previous studies reported that the zerumbone compound has excellent anti-bacterial inhibitory properties in gramnegative and gram-positive microorganisms, such as Escherichia coli (Moreira Da Silva et al, 2018).…”
Section: Introductionmentioning
confidence: 99%